2014
DOI: 10.2147/clep.s66677
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of observational studies in a drug-safety systematic review, comparison of two tools: the Newcastle–Ottawa Scale and the RTI item bank

Abstract: BackgroundThe study objective was to compare the Newcastle–Ottawa Scale (NOS) and the RTI item bank (RTI-IB) and estimate interrater agreement using the RTI-IB within a systematic review on the cardiovascular safety of glucose-lowering drugs.MethodsWe tailored both tools and added four questions to the RTI-IB. Two reviewers assessed the quality of the 44 included studies with both tools, (independently for the RTI-IB) and agreed on which responses conveyed low, unclear, or high risk of bias. For each question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
281
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(283 citation statements)
references
References 34 publications
1
281
0
1
Order By: Relevance
“…In a recent comparison study, the RTI item bank was found to provide a more complete quality assessment than the Newcastle-Ottawa Scale [18,19]. In line with the developer's instructions, the tool was tailored to match the review topic and designs of the included studies.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent comparison study, the RTI item bank was found to provide a more complete quality assessment than the Newcastle-Ottawa Scale [18,19]. In line with the developer's instructions, the tool was tailored to match the review topic and designs of the included studies.…”
Section: Methodsmentioning
confidence: 99%
“…The Newcastle-Ottawa-Scale (NOS) was developed by the University of Newcastle and the University of Ottawa to evaluate the quality of nonrandomized studies to be included in meta-analyses [26,27]. The quality of each eligible study was estimated by using the NOS for case-control or cohort studies, with a range from 0 to 9 [28].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The quality of the studies was evaluated using the Newcastle-Ottawa scale (NOS) [11]. The scale consists of eight items that cover three aspects: selection (representativeness of the exposed cohort, selection of the nonexposed cohort, ascertainment of exposure, demonstration that outcome of interest was not present at start of study); comparability of cohorts on the basis of the design or analysis; and outcome (assessment of outcome, length of follow-up, adequacy of follow-up of cohorts).…”
Section: • Study Quality Assessment and Selectionmentioning
confidence: 99%